Ethnicization of Kenyan Presidential Elections in 2017 - Piotrowska, Maria (Africana Studia, 2020)
The article investigates the efficiency of the centripetal requirement of the territorial distribution of votes in the presidential elections in Kenya. This is power-sharing response to ethnic division in the country and its electoral clashes, tribalism and polarization of the political scene. By analyzing the presidential election results since 1992, I argue that the introduced judicial solutions (including Constitutional reform in 2010), fail to alter ethnical voting pattern and elect pan-ethnic president.